The Effect of 12 Weeks Functional Training on Dynamic Balance in Healthy Older Women - Behnam Gasemi; Akbar Azamian Jazi; Parasto Noori (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: Falling in the elderly is common and dynamic balance has direct effect Abstract  on it. Therefore, we decided to study the effect of functional training on dynamic balance in healthy elderly women. Methods & Materials: Thirty healthy elderly women were purposefully selected as subjects and then randomly divided into two equal groups (control and experimental groups). The dynamic balance was measured by functional test (TUG). The control group didn’t participate in any exercise training, but the experimental group performed functional training for 12 weeks. Differences between the pre and post tests were tested with a paired t-test and the differences between the two groups were tested with an independent t-test. The criterion for significance was set at P>0.05. Results: Dynamic balance didn’t have any significant changes following functional training after 12 weeks in control groups (P=0.11). The time of TUG test as a dynamic balance index, in the within and between groups analysis, in the experimental groups significantly decreased (P=0.000). Conclusion: Functional training can effectively improve dynamic balance and so can play a significant role in healthy life in older women.